Annual Plan 2001-2002 Government of Punjab - Planning Commission (Planning Commission, 2001)
Punjab's economy is predominantly rural based with agriculture sector, including livestock, forming nearly 40 percent of the GDSP. However, agricultural production/ productivity in the State has almost reached a plateau and a strategy needs to be formulated for diversifying out of the wheat-paddy rotation and ensuring value addition through agro-processing of agricultural produce, particularly horticulture and social forestry. In fact, over the years, the contribution of agriculture and livestock to the GDSP of the State has shown a downward trend while that of the secondary sector, particularly, the small scale industry has shown considerable improvement. Unfortunately, the contribution of the tertiary (Services) sector has not shown any increase but, on the contrary, has a shown a downward trend. the overall growth rate of GSDP at constant prices for the 9th Plan is projected at 4.51 % as against the growth rate of 4.70% during the 8th plan.
Government of Punjab Department of Planning